Perkembangan Pemeriksaan Interferon-Gamma Release Assay (IGRA) dengan Metode T-SPOT.TB serta Aspek Klinis Pelaporan Hasil - Dewi, Juliani (PT Dexa Medica, 2020)
Latent tuberculosis infection (LTBI) screening and its treatment play important role in controlling tuberculosis (TB). Healthcare workers are known to be at high risk of latent TB infection. CDC suggests that every healthcare service should have TB controlling program. CDC recommends IGRA test for people who have history of contact with atypical mycobacteria patiens, screening in pregnancy, healthcare worker screening, and serial evaluation for Mycobacterium tuberculosis (MTB) infection. IGRA test kits that are commercially available are QFT and T-SPOT.TB. Term “indeterminate” is used as a borderline value in QFT, but in T-SPOT.TB, it means the result is invalid. Term